Kerajinan Memayet Perempuan Dayak Pampang sebagai Bentuk Penguatan Budaya terhadap Ekonomi Keluarga - Nabillah Kurniati; Syaiful Arif (Jurnal Wanita dan Keluarga, 2023)
This study aims to convey that Pampang Dayak traditional women with carving crafts have cultural awareness. Women who are often misunderstood can only have power in domestic affairs. In fact, women or like men have the same freedom of choice and responsibility. Customary regulations are often seen as a form of shackles to women's self-freedom. However, when the customary system has elements of gender justice in the division of tasks between men and women, a powerful customary social order will be formed. The method used by the author is ethnography, through an empirical approach by interviewing Dayak bead craftsmen. The results of the study show that the creativity and productivity of Pampang Dayak women have succeeded in empowering and strengthening the economy for their families. The great opportunity for economic turnover through the cultural tourism sector is well read by Pampang Dayak women, both in making crafts and traditional banquets. The movement of the family economy and traditional tourism festivals will have a rotational impact on the culture of the Pampang Dayak Village to further develop